Hubungan antara personaliti big five dan daya ketahanan mahasiswa semasa pandemik Covid-19 - Siti Khumairah Chua Abdillah; Agnis Sombuling; Endang Poerwanti (Fakulti Psikologi dan Pendidikan, 2021)
Attitude towards COVID-19 Vaccination Program was carried out to the targeted community of residents from Rumah Panjang Stanley Jelian, Penasu, Sibu, Sarawak. The program was conducted virtually via an online video communication platform. This paper aims to identify the difference between the affective, behaviour, cognitive components, and the overall attitude towards COVID-19 vaccination of participants before and after the attitude change program. A self-administered questionnaire was designed to measure participants’ attitude towards COVID-19 vaccination at two different times. Three scales used were the ABCs components of attitude respectively: affective, behaviour and cognitive. The Yale attitude change approach was applied throughout the program in order to persuade the audience to receive COVID-19 vaccine. The results of the study showed good reliability and validity for both pre- and post-program. As for the analysis of paired sample t-test, a comparison between the pre- and post-program attitude components and attitude as a whole revealed that the participants' attitude toward COVID-19 vaccination had changed significantly. The study's findings revealed the expectation of the attitude change program to positively change the negative attitude of participants towards COVID-19 vaccination had been met. This program and study have illustrated the target community’s attitude towards the COVID-19 vaccination along with their increased acceptance towards the COVID-19 vaccine at the end of the program.